A retrospective study assessing the accuracy of [18F]–fluorocholine PET/CT for primary staging of lymph node metastases in intermediate and high-risk prostate cancer patients undergoing robotic-assisted laparoscopic prostatectomy with extended lymph node dissection. (4th July 2021) - Puterman, Christopher; Bjöersdorff, Mimmi; Amidi, Jennifer; Anand, Aseem; Soller, Wolfgang; Jiborn, Thomas; Kjölhede, Henrik; Trägårdh, Elin; Bjartell, Anders
Abstract: Background: Previous studies have investigated [18F]-fluorocholine (FCH) positron emission tomography with computed tomography (PET/CT) in primary staging of men with intermediate or high-risk prostate cancer and have generally shown high specificity and poor sensitivity. FCH PET/CT is not recommended for the primary staging of metastases in the European guidelines for prostate cancer. However, it has been an option in the Swedish recommendations. Our aim was to assess PET/CT for primary staging of lymph node metastases before robotic-assisted laparoscopic prostatectomy (RALP) with extended pelvic lymph node dissection (ePLND) in patients with intermediate or high-risk prostate cancer. Method: We identified all men with prostate cancer undergoing FCH PET/CT for initial staging followed by RALP and ePLND at Skåne University Hospital between 2015 and 2018. The result from PET/CT scan was compared with pathology report as the reference method for calculation of sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Results: In total, 252 patients were included in the final analysis. Among 85 patients with a suspicion of regional lymph node metastases on FCH PET/CT only 31 had pathology-proven metastases. The sensitivity was 43% (95% CI 0.32–0.55) and the specificity 70% (95% CI 0.63–0.76) for PET/CT to predict lymph node metastases. PPV was 36% and NPV was 75%. Risk group analyses showed similar results. Conclusion: Our study emphasizes the poor performance of FCH PET/CT to predict lymph node metastasis in intermediate and high-risk prostate cancer. The method should be replaced with newer radiopharmaceuticals, such as prostate-specific membrane antigen ligands.